(untitled) (Research, Society and Development, 2021)
Objective: To report the main biological activities of Agave sisalana, describing details of its botanical classification, aspects of chemical and bioactive composition, in addition to highlighting its use as an antimicrobial. Methodology: This is a literature review of a descriptive character with a qualitative approach, elaborated through the analysis of materials indexed in the platforms: SciELO, PubMed and the portal of CAPES journals, published between the years 2002 to 2021, written in languages: Portuguese, English and Spanish. After applying the inclusion and exclusion criteria, as well as reading the materials, 38 contents were selected for the composition of this study. Results and discussion: The bioactive activity of Agave sisalana, is linked to the components of its secondary metabolism, where it can be measured: alkaloids, coumarins, tannins and saponins. With regard to sisal saponins, they are identified as having antifungal and antibacterial action, especially against pathogenic microorganisms. In addition to the actions mentioned, studies have shown their effects such as: insecticide, larvicide, ovicide, antiparasitic, antioxidant, immunomodulator, analgesic, anti-inflammatory, under behavioral and neurochemical activity, as well as in chemoprevention and cancer control. Conclusion: The applications of Agave sisalana are varied, whether in the industrial, therapeutic artisanal or in agriculture. Its antimicrobial activity is scientifically proven, whether in the inference of fungi or bacteria, making this an important alternative, in view of the incidence of resistant microorganisms.